ANALYSIS OF EMPLOYEE WORKING LOAD IN BINA MANDIRI GORONTALO UNIVERSITY USING FULL TIME EQUIVALENT METHOD - Nur Naningsih Daud; William I. S. Mooduto; Djamila Podungge (Jurnal Ilmu Manajemen dan Bisnis, 2022)
This study aims to determine the workload of each employee at Bina Mandiri University Gorontalo. This research uses descriptive research. Respondents of this study were 38 people who were employees of the Bina Mandiri Gorontalo Campus. Data analysis used Full Time Equivalent (FTE). The results showed that the workload of Bina Mandiri University Gorontalo employees using the FTE method, of the 38 employees there were 30 employees who had normal workloads, 8 employees had underloaded workloads, and no employees had overloaded workloads.